Pengaruh Motivasi, Lingkungan Kerja, dan Kepuasan Kerja Terhadap Kinerja Karyawan PT. Sumber Masanda Jaya Brebes: (Studi Kasus Gedung Bottom 1) - Lina Merliana; Nurkhojin; Nur Afridah (CV. KAMPUS AKADEMIK PUBLISING, 2024)
This research aims to analyze the influence of motivation, work environment and job satisfaction on employee performance at Pt. Sumber Masanda Jaya Brebes Gedung Bottom 1. The type of research used in this research is quantitative research with an Ex Post Facto method approach. The population of this study were employees of Pt. Sumber Masanda Jaya Brebes in the Bottom 1 Building has 85 employees. Data collection techniques use observation and questionnaires. Observation is used to make observations and record the number of employees. The questionnaire was used to reveal the influence of motivational variables, work environment and job satisfaction on employee performance, then data processing used the SPSS (statustic package for the social sciences) 22 for Windows software program. The results of the research state that the motivation variable (X1) does not have a significant effect on employee performance, this is proven by the t value of 0.0222 < t table of 0.1990 with a significant value of 0.825 > 0.05. The work environment variable (X2) has a significant effect on employee performance, this is proven by the t value of 0.5304 < t table of 0.1990 with a significant value of 0.000 > 0.05. The job satisfaction variable (X3) has a significant effect on employee performance, this is proven by the t value of 0.2027 < t table of 0.1990 with a significant value of 0.046 > 0.05.